Detection of the insulating gap and conductive filament growth direction in resistive memories. Issue 37 (3rd September 2015) - Yalon, E.; Karpov, I.; Karpov, V.; Riess, I.; Kalaev, D.; Ritter, D.
Abstract : The insulating gap and conductive filament growth direction in valence change RRAM devices were studied using the metal-insulator-semiconductor bipolar transistor structure. Abstract : Filament growth is a key aspect in the operation of bipolar resistive random access memory (RRAM) devices, yet there are conflicting reports in the literature on the direction of growth of conductive filaments in valence change RRAM devices. We report here that an insulating gap between the filament and the semiconductor electrode can be detected by the metal–insulator–semiconductor bipolar transistor structure, and thus provide information on the filament growth direction. Using this technique, we show how voltage polarity and electrode chemistry control the filament growth direction during electro-forming. The experimental results and the nature of a gap between the filament and an electrode are discussed in light of possible models of filament formation.